Landscape footprints of peopling and colonisation from the Late Bronze Age to Antiquity in the coastal hinterland of Emporion-Emporiae, NE Iberia. (April 2022) - Ejarque, Ana; Julià, Ramon; Castanyer, Pere; Orengo, Hector A; Palet, Josep Maria; Riera, Santiago
The Empordà plain attests to a remarkable mixture of Late-Holocene cultural exchanges and colonial processes. This includes the founding of Emporion, the earliest Greek colony in Iberia, and of the Roman city of Emporiae . This study aims at assessing landscape changes related to indigenous and colonial settlement in this unique scenario where the shaping of cultural landscapes occurred within a dynamic coastal ecosystem. We carried out a high-temporal resolution palaeoenvironmental study in Els Estanys, a palaeowetland located in the vicinity of Emporion-Emporiae . Palynological, sedimentological and geochemical indicators were coupled with available archaeological and archaeobotanical data-sets. Between 1100 and 800 cal BC, the settling of Urnfield Late Bronze societies resulted in the sustained clearance of woodlands and moderate agropastoral exploitation of coastal ranges. During this period, marine-influenced lagoonal areas were poorly exploited. During the Iron Age (800–450 cal BC), a threshold in the landscape construction of the area occurred with the first pastoral exploitation of lagoonal areas, intensified cereal cultivation, controlled burning, and enhanced deforestation following the settlement of Iberian groups. Greek colonisation (580–200 cal BC), did not trigger intensified farming exploitation or landscape clearance, nor did it imply the introduction of new land uses or crops in the hinterland. Exploitation of the latter continued relying on cereal cultivation and grazing, as before, suggesting the permanence of indigenous landscapes and practices in the hinterland. To the contrary, urban and periurban landscapes played a significant role in the construction of the colonial landscape with the introduction of olive groves likely as ornamental trees. Roman conquest and colonisation of the area constituted a new threshold in the occupation and management of the hinterland with (1) intensified rural settlement; (2) expansion of wet pastures and removal of littoral woodlands; (3) development of diversified cropping activities; and (4) development of mining and smelting activities.